FAKTOR-FAKTOR YANG MEMPENGARUHI PASIEN DALAM PEMANFAATAN RAWAT JALAN DI UPT PUSKESMAS CONCONG LUAR - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this study is to describe the factors that influence patients in the use of outpatient care at UPT Puskesmas Concong Luar. This research is a quantitative descriptive study. The number of samples is 100 respondents. In this study the independent variables are Facilities, Doctor Services, Nurse Services or Midwives, Affordability of service costs, Ease of information and dependent variable utilization of outpatient services. The results showed that the facilities partially influenced outpatient utilization. Doctor services have a partial effect on the use of ambulatory care. Nurse services have a partial effect on the use of ambulatory care. Service costs do not affect the utilization of outpatient care. Ease of information affects the use of ambulatory care. The results of the coefficient of determination test indicate that the influence of Facility, Doctor Service, Nurse or Midwife Services, Affordability of service costs, Ease of information on outpatient utilization by 63.2%, while the remaining 36.8% can be explained by other variables outside of the research variables.